Kenduri Kematian Menurut Persepsi Dosen IAIN Sulthan Thaha Saifuddin Jambi - Sulaiman, M. Saman (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2008)
The moslems have done the death feast practice (Kenduri Kematian) since a long time ago, if it refered to classical and contemporary fiqh books, there is no scholar of moslems that suggested this tradition. On the contrary, they prohibit and carp it. IAIN STS Jambi is islamic college that represent the place of masters in islamic theologt. To the lecturers that have competence are asked their views about the practice of Kenduri Kematian which they perceive by thentselves and related to knowledge. As the result of this research, most of them refuse this tradition because it is not based on syari. The data presentation is in the form of naration which is written expression tofollow responders opinion easily.